YIIFSWA II OPENDAY - Interview with Connie Aku Nyador - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early seed yam